Characterization of cold background plasma during the runaway electron beam mitigation experiments in the JET tokamak. (31st July 2020) - Sridhar, S.; Reux, C.; Beyer, P.; Lehnen, M.; Coffey, I.; Guirlet, R.; Fedorczak, N.
Abstract: Disruptions are a major threat to future tokamaks including ITER. They generate excessive electromagnetic forces, heat loads and multi-MeV runaway electrons. The runaway electron beam carries the risk of in-vessel component damage and even the structures beyond them. Thus, prevention of the runaway beam generation or the mitigation of the developed beam is of prime importance. In JET ITER-like wall, the runaway electron beams triggered by massive gas injection (MGI) coexists with a cold background plasma. Lines corresponding to the higher ionization states of argon are observed in VUV spectra outside of the runaway region suggesting a hot background plasma.Using the quantitative analysis of the VUV spectroscopy, the temperature profiles of the background plasmas are estimated using a synthetic line ratios method. The background plasmas at JET-ILW are found to be hotter than other tokamaks where mitigation of the runaway electron beam was unconditionally successful. The volume-averaged T e is found to increase linearly with the gas amount used to trigger the disruption and the electron density in the far scrape-off layer. It is independent of other background plasma properties. A 0D/1D power balance of the post-disruption physical systems is made using the characteristics of the background plasma. The collisional power loss of the runaway electron beam is the primary power source heating the background plasma.